2007
DOI: 10.1203/pdr.0b013e31813cbe8b
|View full text |Cite
|
Sign up to set email alerts
|

Could Preference for Palatable Foods in Neonatally Handled Rats Alter Metabolic Patterns in Adult Life?

Abstract: ABSTRACT:Previous studies indicate that, in adulthood, neonatally handled rats consume more sweet food than nonhandled rats. The aim of the present study was to assess the effects of the chronic exposure to a palatable diet (chocolate) in adult neonatally handled rats. We measured the consumption of foods (standard lab chow and chocolate), body weight gain, abdominal fat deposition, and levels of plasma lipids, glucose, insulin, and corticosterone in adult neonatally handled (10 min/d, first 10 d of life) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 32 publications
3
16
1
Order By: Relevance
“…These animals also ingest more palatable pellets than controls when exposed to them either in a test apparatus (Silveira et al, 2004, 2008; Benetti et al, 2007) or in the homecages (Silveira et al, 2006), without differences in the consumption of regular lab chow or fiber pellets. However, satiety to sweet food seems to be adequate in neonatally handled rats (Silveira et al, 2006).…”
Section: Methodsmentioning
confidence: 95%
See 1 more Smart Citation
“…These animals also ingest more palatable pellets than controls when exposed to them either in a test apparatus (Silveira et al, 2004, 2008; Benetti et al, 2007) or in the homecages (Silveira et al, 2006), without differences in the consumption of regular lab chow or fiber pellets. However, satiety to sweet food seems to be adequate in neonatally handled rats (Silveira et al, 2006).…”
Section: Methodsmentioning
confidence: 95%
“…However, when exposed to predators, handled animals may be less fearful and therefore more vulnerable than their non‐handled counterparts (Padoim et al, 2001). Concerning feeding behavior, neonatally handled animals seem to be less prone to suffer the metabolic consequences of being exposed chronically to a highly palatable diet (Benetti et al, 2007). However, it remains to be established if the concomitant exposure to different types of palatable food would affect these animals in a different way in comparison to non‐handled ones.…”
Section: Methodsmentioning
confidence: 99%
“…This ontogenetic pattern corroborates the clinical literature, which suggests that eating disorders like anorexia nervosa and bulimia emerge after puberty (Fairburn & Harrison, 2003). Furthermore, neonatal handling seems to affect only a few metabolic parameters: plasma levels of ghrelin and triglycerides are decreased, but there is no change in insulin, leptin, glucose, or cholesterol levels (Benetti et al, 2007; Silveria et al, 2006). These studies indicate that the neonatal handling model provides an approach for understanding mechanisms underlying the enduring consequences of early experience on the individual’s responses to food.…”
Section: Neonatal Handling and Food Consumptionmentioning
confidence: 99%
“…In addition, neonatally handled rats exhibit increased consumption of palatable foods during acute exposure to this type of food (Silveira et al, 2006; da Silva Benetti et al, 2007). In our previous studies, we described a protective influence of neonatal handling on abdominal fat deposition (da Silva Benetti et al, 2007) in female rats after a chronic exposure to a highly palatable, highly caloric diet. Therefore, it was suggested that a specific metabolic response to chronic highly caloric diets could protect handled females from the harmful effects of this environmental challenge in adulthood.…”
Section: Introductionmentioning
confidence: 99%